Removal of Contaminant under Different Hydraulic Loading Rate in Constructed Wetland - Wang, Hao; Chen, Jianwei; Li, Xuejin (Asian Journal of Chemistry, 2013)
In Tangshan area of China, the secondary effluent of wastewater treatment plants was used for this study. Horizontal zeolite wetland was carried out treating it. Hydraulic loading rate was the parameters for analyzing the nitrogen and phosphorus removal efficiency of pollutants from the secondary effluent of wastewater treatment plant. Zeolite constructed wetlands showed different behaviours for nitrogen and phosphorus removals. Under the optimum hydraulic loading rate, the primary pollutions were removed to a large extent.